2018
DOI: 10.1038/s41408-018-0139-7
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes play a role in multiple myeloma bone disease and tumor development by targeting osteoclasts and osteoblasts

Abstract: Progression of multiple myeloma (MM) is largely dependent on the bone marrow (BM) microenvironment wherein communication through different factors including extracellular vesicles takes place. This cross-talk not only leads to drug resistance but also to the development of osteolysis. Targeting vesicle secretion could therefore simultaneously ameliorate drug response and bone disease. In this paper, we examined the effects of MM exosomes on different aspects of osteolysis using the 5TGM1 murine model. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
124
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 30 publications
1
124
0
Order By: Relevance
“…We also found that the development of resistance conferred by exosomes could be inhibited by GW4869, possibly due to the blockade of exosome secretion by donor cells. GW4869 has already been used in vivo to inhibit exosome secretion in different disease models, and combination treatment with bortezomib led to a significant effect on tumor load …”
Section: Discussionmentioning
confidence: 99%
“…We also found that the development of resistance conferred by exosomes could be inhibited by GW4869, possibly due to the blockade of exosome secretion by donor cells. GW4869 has already been used in vivo to inhibit exosome secretion in different disease models, and combination treatment with bortezomib led to a significant effect on tumor load …”
Section: Discussionmentioning
confidence: 99%
“…They revealed that DKK‐1 transfer resulted in a decrease in Collagen 1A1, Osterix, and Runx2 in OBs. Of note, they demonstrated that exosomes could mediate osteolysis in a similar pattern as the MM cells . Inhibition of the secretion of exosomes by the sphingomyelinase inhibitor GW4869 enhanced cortical bone volume and increased the sensitization of MM cells to bortezomib, resulting in a significant antitumor response when bortezomib and GW4869 were combined .…”
Section: Exosomes and MMmentioning
confidence: 95%
“…116 Overall, their findings showed that a crucial role for exosomes in the BM microenvironment and proposed a new therapeutic target for anti-MM therapy. 116 MiRNAs are important cargos that could be transferred by exosomes. It has been found that miR-340 transfection into BM-derived exosomes restores antiangiogenic features, which suggests that the replacement of exosomal miRNAs could have therapeutic benefits.…”
Section: Exosomes and MMmentioning
confidence: 97%
See 2 more Smart Citations